Management leading & collaborating in a competitive world - Bateman, Thomas S.; Konopaske, Robert; Snell, Scott (McGraw-Hill Education, 2021)
"Welcome to our 14th edition! Thank you to everyone who has used and learned from previous editions. We are proud to present to you our best-ever edition. Our mission with this text is to inform, instruct, and inspire. We hope to inform by providing descriptions of the important concepts and practices of modern management. We hope to instruct by describing how you can identify options, make decisions, and take effective action. We hope to inspire not only by writing in an interesting way but also by providing a real sense of the challenges and fascinating opportunities ahead of you. Whether your goal is starting your own company, leading a team to greatness, building a strong organization, delighting your customers, or generally forging a positive and sustainable future, we want to inspire you to take meaningful action"--